2015
DOI: 10.1371/journal.pone.0120623
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients with Primary Cutaneous Amyloidosis

Abstract: BackgroundPrimary cutaneous amyloidosis (PCA) is a relatively rare and itchy skin disorder characterized by amyloid deposits in the superficial dermis. The cosmetic disfigurement and severe pruritus dramatically affects the patient’s quality of life. In spite of the prevalence of the disease in China, the quality of life (QoL) impact of the PCA has not been well defined and is the focus of this study.ObjectiveTo examine the HRQoL of patients with PCA and to evaluate the association between HRQoL scores, diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…OSMR β and IL31RA code for the subunits of the IL‐31 receptor. Its ligand, IL‐31, has been shown to be an important cytokine underlying various itchy dermatoses, such as AD, and we have previously found a significant clinical association between PLCA and AD . In this study, we found increased epidermal expression of IL‐31 receptors in PLCA lesions without an increase in IL‐31 levels in the skin and blood of patients.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…OSMR β and IL31RA code for the subunits of the IL‐31 receptor. Its ligand, IL‐31, has been shown to be an important cytokine underlying various itchy dermatoses, such as AD, and we have previously found a significant clinical association between PLCA and AD . In this study, we found increased epidermal expression of IL‐31 receptors in PLCA lesions without an increase in IL‐31 levels in the skin and blood of patients.…”
Section: Discussionsupporting
confidence: 49%
“…Pruritus is present in 60–90% of PLCA lesions, and our local series revealed a prevalence of 68·2% . Although the itch is localized, the intensity of pruritus can be severe and impairs the quality of life of patients . Currently, the pathophysiology of pruritus in these patients is largely unknown.…”
mentioning
confidence: 78%
“…The involvement of other internal organs is absent due to the local synthetization and deposition of the proteic aggregates; therefore, it does not imply a vital risk [1,2,3]. However, the impact on the quality of life can be significant, whereas intense pruritus is frequently associated and the skin appearance might be perceived as unpleasant [3,4]. Clinical features of PCA define the three subtypes of the disease: macular, papular (lichenoid form), and nodular amyloidosis [1,2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of patients of postinflammatory hyperpigmentation did not show any significant effect on their quality of life in this study in contrast to our study which could be due to different inclusion criteria as we included female patients with hyperpigmentation involving exposed areas . In another study of health‐related quality of Life in patients with primary cutaneous amyloidosis, cosmetic disfigurement and severe pruritus dramatically affected patient's quality of life in MA, which led to psychosocial stress and the impairment of emotional functioning . Patients with primary cutaneous amyloidosis experienced a significant impairment of life quality in terms of feelings, clothing, social, and leisure activities and daily routine.…”
mentioning
confidence: 99%